2021
DOI: 10.1039/d1ra01870a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fluorinated graphene-modified epoxy coatings on the corrosion behaviour of 2024 aluminium alloy

Abstract: This study provides an enhanced corrosion resistance of epoxy resin (EP) by embedding fluorinated graphene (FG) into the epoxy matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…However, coating 4 still presented one time constant, demonstrating that flake aluminum and spherical aluminum synergistically enhanced the shielding effect, so the corrosive medium was not easy to diffuse and the substrate was not corroded. In addition, the low frequency impedance modulus (|Z| 0.01Hz ) can be used as a vital parameter to further characterize the shielding performance of the composite coatings, 43 as shown in Figure 11d–f. Compared with other three types of coatings, coating 1 exhibited lower |Z| 0.01Hz values throughout the immersion times.…”
Section: Resultsmentioning
confidence: 99%
“…However, coating 4 still presented one time constant, demonstrating that flake aluminum and spherical aluminum synergistically enhanced the shielding effect, so the corrosive medium was not easy to diffuse and the substrate was not corroded. In addition, the low frequency impedance modulus (|Z| 0.01Hz ) can be used as a vital parameter to further characterize the shielding performance of the composite coatings, 43 as shown in Figure 11d–f. Compared with other three types of coatings, coating 1 exhibited lower |Z| 0.01Hz values throughout the immersion times.…”
Section: Resultsmentioning
confidence: 99%
“…FG was synthesized according to the method reported in the literature, and the F/C ratio is 28.19%. 28…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the research results also pointed to the influence factor of FG on the long-term performance of modified coatings to the compatibility between nanofillers and resins. 28,29 Therefore, improving the interfacial compatibility between nanofillers and EP is an effective way to obtain anticorrosion coatings with better performance. Wang et al 30 reported a method for covalent modification of graphene oxide with dopamine, which effectively improved the compatibility between nanofillers and resins.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al examined the anticorrosive performance of FG incorporated epoxy matrix on 2024 aluminum alloy. [101] The FG in epoxy increased the hydrophobicity and corrosion resistance capability. The anticorrosive performance of 2 wt% fluorine content FG in epoxy coating was thrice compared to the virgin epoxy coatings with improved contact angle.…”
Section: Biomedicalmentioning
confidence: 99%